The influence of community empowerment based on theory of planned behavior towards the knowledge and attitude of mothers with tuberculosis - Sianturi, Efendi; Pasaribu, Rina Doriana; Pardosi, Maida; Alfrianne, Alfrianne; Surbakti, Elisabeth (Science Midwifery, 2024)
Healing Tuberculosis takes quite a long time. Therefore, the role of family and community in caring for sufferers is significant. The research aims to empower the community through a behavioral belief factor approach, namely behavioral control in the Theory of Planned Behavior model, to increase the self-efficacy of the target, namely mothers suffering from Tuberculosis, through increasing the knowledge and attitudes of mothers suffering from Tuberculosis. This research is quasi-experimental. This research was conducted in Pantai Labu Village, Deli Serdang Regency. This research experiment: Health promotion of Tuberculosis by Tuberculosis Ambassadors. Tuberculosis Ambassadors are mothers who have recovered from Tuberculosis and are trained to become agents of Change. The measuring instrument is a questionnaire. Sample Category: Mothers Suffering from Pulmonary Tuberculosis (n=50). Data analysis using the Paired T-test if the data is usually distributed and if the data is not normally distributed, the Wilcoxon test is used. The results show commitment from health cadres as Pulmonary Tuberculosis Ambassadors in Pantai Labu Village. There was an increase in the knowledge and attitudes of mothers with pulmonary Tuberculosis regarding pulmonary Tuberculosis (p-value < 0.05). Tuberculosis Ambassadors are effective as providers of health promotion.